EDUCATING FOR THE INFORMATION SOCIETY - Osmundo Rocha Claudino (Editora da Universidade de Santa Cruz do Sul, 2013)
The emergence of the information society and the implications for the field of education form the object of analysis of this article, therefore, seeks to outline the profile of the model of informational society, since its main historical precedents to its conceptualization. The characterization of the knowledge society, driven by technological change, highlights the rearrangement of the teaching-learning process from the deterritorialization / virtualization, requiring new practical knowledge of the transaction. We conclude that educate in cyberculture implies recognizing the paradigmatic crisis of the educational system, review postures and understand the technological advances as allies of new practices that expand the role of educator and humanitarian vocation to resize a new habitat.